Personalized Treatment of H3K27M-Mutant Pediatric Diffuse Gliomas Provides Improved Therapeutic Opportunities - Gojo, Johannes; Pavelka, Zdenek; Zapletalova, Danica; Schmook, Maria T.; Mayr, Lisa; Madlener, Sibylle; Kyr, Michal; Vejmelkova, Klara; Smrcka, Martin; Czech, Thomas; Dorfer, Christian; Skotakova, Jarmila; et al. (Frontiers in Oncology, 2020)
Diffuse gliomas with K27M histone mutations (H3K27M-glioma) are generally characterized by a fatal prognosis, particularly affecting the pediatric population. Based on the molecular heterogeneity observed in this tumor type personalized treatment is considered to substantially improve therapeutic options. Therefore, clinical evidence for therapy, guided by comprehensive molecular profiling is urgently required. In this study we analyzed feasibility and clinical outcomes in a cohort of 12 H3K27M-glioma cases treated at two centers. Patients were subjected to personalized treatment either at primary diagnosis or disease progression and received backbone therapy including focal irradiation. Molecular analyses included whole-exome sequencing of tumor and germline DNA, RNA-sequencing and transcriptomic profiling. Patients were monitored with regular clinical as well as radiological follow-up. In one case, liquid biopsy of cerebrospinal fluid (CSF) was used. Analyzes could be completed in 83 % (10/12) and subsequent personalized treatment for one or more additional pharmacological therapies could be recommended in 90% (9/10). Personalized treatment included inhibition of PI3K/AKT/mTOR-pathway (3/9), MAPK-signaling (2/9), immunotherapy (2/9), receptor tyrosine kinase inhibition (2/9), and retinoic receptor agonist (1/9). The overall response rate within the cohort was 78% (7/9) including one complete remission, 3 partial responses and 3 stable diseases. Sustained responses lasting for 28 to 150 weeks were observed for cases with PIK3CA mutations treated with either miltefosine or everolimus and additional treatment with trametinib / dabrafenib in a case with BRAFV600E mutation. Immune checkpoint inhibitor treatment of a case with increased tumor mutational burden (TMB) resulted in complete remission lasting for 40 weeks. Median time to progression was 29 weeks. Median overall survival (OS) in the personalized treatment cohort was 16.5 months. Last, we compared OS to a control cohort (n=9) showing a median OS of 17.5 months. No significant difference between the cohorts could be detected but long term survivors (> 2 years) were only present in the personalized treatment cohort. Taken together, we present a first evidence of clinical efficacy and improved patient outcome by a personalized approach at least in selected cases of H3K27M-glioma.